Antibacterial and antiviral potential of Zirconium Oxide nanoparticle using extract of Chloranthus Erectus leaf - Hasan, Nor' Aishah; Wazir, Nurul Natasha; Zainal-Abidin, Nurhamimah; Nawahwi, Mohd Zaini; Badrol Hisham, Nurul Atikah; Yasin, Yamin; Nik Masdek, Nik Rozlin; Khairat, Jasmine Elanie; Yu, Lim Z.H.I.; Mohamad Azzeme, Azzreena; Arief, Syukri; Putri, Gusliani E.K.A.; et al. (Asian Publication Corporation, 2024)
Zirconium oxide nanoparticles (ZrO2 NPs) were synthesized with an effective capping agent using aqueous extract of Chlorentus erectus at the optimized conditions. The aqueous leaf extract contained phytochemical compounds that could regulate the size and shape of the nanoparticles. The average size of C. erectus-ZrO2 NPs crystallite was 10.42 nm, which was determined based on Scherrer Debye’s equation. The finding indicated the effectiveness of the phytochemical compounds to diminish the agglomeration of the particles. The C. erectus mediated ZrO2 NPs were in spherical clusters when observed through a transmission electron microscope (TEM). An elemental energy diffraction X-ray (EDX) assessment also revealed a significant zirconium and oxygen percentage, suggesting that the phytochemicals present in the leaf extract did not alter the purity of C. erectus-ZrO2 NPs. Moreover, 200 µg/mL of synthesized ZrO2 NPs effectively inhibited K. pneumoniae. Up to 300 µg/mL of C. erectus- ZrO2 NPs demonstrated non-toxicity to vero cells and low antiviral properties against the DENV-2 virus when introduced to cells post-infection.